TOXOPJASMAGONDANIA JLLE AND MANCEAUX PADA AYAM BUKAN RAS (GALLUS SP.) DAN BURUNG MERPATI (COLUMBA UNA GMELIN) DIKOTAMADYA BOGOR - Setyorini, L.E; Purwaningsih, E.; Hartini, S.; Aziz, J. (Research Center for Biology-Indonesian Institute of Sciences, 1998)
Using Indirect Hemqiglutination (IHA) test on 26 domesticfowl (Gallus sp.)and domestic pigeon (Columba liviaj were screened